IMPLEMENTASI AUDIT MUTU PEMBELAJARAN BERBASIS RISIKO DALAM PENGUATAN KURIKULUM MERDEKA DI SD DARUL ILMI SURABAYA - Ali, Nurul Fauziah; Kaniati Amalia; Erny Roesminingsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of risk-based learning quality audits at SD Darul Ilmi Surabaya, identify risks in the implementation of learning programs, and analyze strategies for improving learning quality. The research employed a qualitative descriptive approach using document analysis methods. The primary data source was the 2025/2026 curriculum program evaluation report of SD Darul Ilmi Surabaya. Data collection was conducted through documentation studies, while data analysis used the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The research findings indicate that the Independent Curriculum, Deep Learning, Project D3 Young Creator, and STREAM-based STS programs have been systematically evaluated to implement mutual audits of risk-based learning. The research found several positive outcomes, such as improved teacher skills in developing open modules, successful implementation of project-based learning, and integration of STREAM learning. However, the research also identified several issues with learning quality, such as uneven quality of HOT assessments, inconsistent program implementation, insufficient scaffolding during the D3 project design phase, and ineffective learning documentation systems. To address these issues, educational institutions are implementing various initiatives to improve education quality. These include teacher training, the creation of a STREAM-based HOT bank, the development of digital portfolios, and the enhancement of technical elements in STREAM learning. The study concludes that risk-based learning quality audits can serve as a strategic approach to support continuous improvement in elementary school learning quality.